THE IMPORTANCE OF ALCHEBA DRUG IN POST-STROKE APHASIA - Axmedov Shamshod Jamshidovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Alcheba is an independent means of reducing the severity of aphasia, but the best results were achieved by combining them. The effect of taking Alcheb and using it persisted for a long time after the completion of treatment. When analyzing the integral semi-quantitative assessments of the general condition and the cognitive sphere, an increase in the social adaptation of patients was noted, which took place against the background of an improvement in mnestic abilities and concentration of attention. This review considers the role of drug therapy in the treatment of post-stroke aphasia, the evidence for efficacy of different agents, and the theory-based explanations of drug-related benefits for aphasia rehabilitation.